Visiting Taman Ayun Temple, a Bali’s Subak Heritage Temple in Mengwi - Putu Herry Hermawan Priantara (Bali Tourism Journal, 2022)
Subak temple serves as a socio-religious adhesive for agrarian society in carrying out its function as a member of this ancient system. One of the temples with an important function for an agrarian society in the Mengwi area, Badung, is the Taman Ayun Temple. Together with the Ulun Danu Batur Temple, these two holy places have a religious function for the Subak Pakerisan and Subak Catur Angga Batukaru areas. The two areas consist of five broad rice fields with a water distribution area that reaches 19,500 ha. In 1634, Taman Ayun Temple was constructed by order of Mengwi Kingdom, I Gusti Agung Putu after he moved the location of His kingdom from Belayu to Mengwi. Serving as the Paibon Temple for the Mengwi kingdom Royal Family, the Taman Ayun temple was magnificently built as a form of devotion to the royal ancestors. Later on, this temple developed as a Penyawangan for several large temples in Bali, which in the past could not be accessed in a day by the Mengwi people. Taman Ayun Temple also acts as a place to regulate water for the activities of the Subak community around the site. After UNESCO recognized Taman Ayun Temple as part of the manifestation of the Tri Hita Karana philosophy in 2012, the number of visits to Taman Ayun Temple increased significantly. Even though it has become a tourist-visit destination, visitors must obey several things when visiting this cultural heritage site. Apart from that, there are various interesting destinations around Taman Ayun Temple which are also worth visiting by tourists to know more deeply about the culture-based life adopted by the Balinese people.